IMPROVING STUDENTS’ LISTENING SKILL BY USING ENGLISH SONGS - Dadang Solihat; Prita Lusiana Utami (University of Kuningan, 2014)
Abstract: This study investigates students’ listening skill by using English songs. The reason of choosing this topic is based on the problems that is listening skill. It can be seen during the writer teaching at SMPN in Kuningan, the students lack of listening skill. The aims of this research were to investigate the effectiveness of using English songs to improve students listening skill and to know the students attitudes of using English songs in listening skill.The target of this research was the students at eighth grade of SMPN 1 Lebakwangi, Kecamatan Lebakwangi. There were 62 students. The method of this research was quasi-experimental design. There are two groups as the investigated group in this research. One group is for experimental group and the other group is controlled group. The data were collected through three steps, namely pre-test, post-test, and questionnaire. To analyze the result of pre test and post test, this research used t-test formula computed by SPSS 17.00. The result of the research showed that the students’ progress in mastering listening skill during the activity can be seen from the Paired test that shows t count is higher than t table (-32.6972.042). It indicates that English songs is effective in listening skill. Students given positive attitude based on the questionnaire result that it had level agreement 92% and mean 142.Keywords: listening skill, song, media, language skill